Isotherm Models for Predicting the Dye Adsorption Potential of Coon Tail and Water Milfoil - Olcayto Keskinkan (Adsorption Science & Technology)
The dye adsorption potential and characteristics of the submerged aquatic plants Ceratophyllum demersum and Myriophyllum spicatum were investigated using an azo dye (Basic Blue 41 – BB41). Adsorption equilibria were attained after 160 min at various initial BB41 concentrations (in the range 5–80 mg/l). Attempts were made to fit the equilibrium data obtained using the Langmuir, Freundlich, Redlich–Peterson, Temkin and Dubinin–Radushkevich adsorption isotherm models. The data obtained from the C. demersum and M. spicatum studies were fitted exactly by the Redlich–Peterson and Temkin adsorption isotherms models with correlation coefficient (r) values of 0.999 and 0.981, respectively. The fits of the Langmuir and Freundlich adsorption isotherm models were also acceptable. Evaluation of the experimental data using the Langmuir equation revealed that the maximum adsorption capacities of C. demersum and M. spicatum were 50.0 mg/g and 64.9 mg/g, respectively.